An Introduction to Sports Concussions - Giza, Christopher C. (Continuum (Minneap Minn), 2014)
PURPOSE OF REVIEW: Concussions are a major public health issue, and particularly so in the setting of sports. Millions of athletes of all ages may face the risks of concussion and repeat concussion. This article introduces the terminology, epidemiology, and underlying pathophysiology associated with concussion, focused on sports-related injuries. RECENT FINDINGS: Concussion is a clinical syndrome of symptoms and signs occurring after biomechanical force is imparted to the brain. Because of the subjective nature of symptom reporting, definitions of concussion differ slightly in different guidelines. Concussion nomenclature also includes mild traumatic brain injury, postconcussion symptoms, postconcussion syndrome, chronic neurocognitive impairment, subconcussive injury, and chronic traumatic encephalopathy. Between 1.6 and 3.8 million sports-related concussions are estimated in the United States annually, particularly in youth athletes. Rates of concussion are higher in sports such as football, rugby, ice hockey, and wrestling in males, and soccer and basketball in females. The underlying pathophysiology of concussion centers on membrane leakage, ionic flux, indiscriminate glutamate release, and energy crisis. These initial events then trigger ongoing metabolic impairment, vulnerability to second injury, altered neural activation, and axonal dysfunction. While the linkage between acute neurobiology and chronic deficits remains to be elucidated, activation of cell death pathways, ongoing inflammation, persistent metabolic problems, and accumulation of abnormal or toxic proteins have all been implicated. SUMMARY: Concussion is a biomechanically induced syndrome of neural dysfunction. Millions of concussions occur annually, many of them related to sports. Biologically, a complex sequence of events occurs from initial ionic flux, glutamate release, and axonal damage, resulting in vulnerability to second injury and possibly to longer-term neurodegeneration.